Potential role of dietary pomegranate seed powder (PSP) (Punica granatum L.) and / or Saccharomyces cerevisiae (SC) on lipid profile of Local male lambs - al-Musodi, Mohanad Fadhl Hussain; Al-Zwean, Drgham Hamza Yousif (Journal of Kerbala for Agricultural Sciences, 2023)
This study was conducted to find out the effect of adding pomegranate seeds (PSP) and Saccharomyces cerevisiae (SC) to the diet of local lambs on their lipid profiles. (Total Cholesterol (TC), Triglyceride (TG), High Density Lipoprotein (HDL-C), Low Density Lipoprotein (LDL-C), and Very Low Density Lipoprotein (vLDL-C)) It was implemented in the animal field of Baghdad University’s veterinary medicine college and ran from 12/1/2022 to 12/6/2022, with 20 lambs aged 2-3 months divided into four groups, with G1 serving as the control group fed concentration diets. G2 fed the same ration and 3% dried pomegranate seed pomace powder (PSP), G3 fed the same ration and 4% PSP with 3g of Saccharomyces cerevisiae (SC), and G4 fed the same ration and 6% PSP with 3g of Saccharomyces cerevisiae (SC), water supply at Libdum . Samples of blood were taken from all lambs monthly to measure some biochemical characteristics, including total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C), and very-low-density lipoprotein (VLDL-C) statistically significant differences (P < 0.05) were discovered in the results of The administration of PSP and SC with diets revealed a remarkable effect between treated and untreated groups for lipid profile aspects in some periods of the experiment when compared to the control group, so it could be concluded from this study that using PSP and/or SC to treat groups could contribute to improving lipid profile traits in male lambs